2021
DOI: 10.1007/s11748-021-01599-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative use of furosemide may increase the incidence of acute kidney injury after coronary artery bypass grafting: a propensity score-matched study

Abstract: Objectives Furosemide is usually administered before the Coronary artery bypass grafting (CABG) to improve water–sodium retention. However, no final conclusions are available on the postoperative renal outcome of furosemide. We evaluated the effect of preoperative furosemide on acute kidney injury (AKI) after CABG. Methods We recorded the use of furosemide 14 days before surgery in all patients who underwent CABG from 2016 to 2017. Patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Other authors found no benefit of furosemide use in the perioperative period, including no difference in the need for renal replacement therapy after the surgery [123][124][125]. Zheng et al [126] found that preoperative use of furosemide was associated with higher CSA-AKI risk.…”
Section: Fluid Balance and Osmotic Regulationmentioning
confidence: 98%
“…Other authors found no benefit of furosemide use in the perioperative period, including no difference in the need for renal replacement therapy after the surgery [123][124][125]. Zheng et al [126] found that preoperative use of furosemide was associated with higher CSA-AKI risk.…”
Section: Fluid Balance and Osmotic Regulationmentioning
confidence: 98%
“…Furthermore, a prospective cohort study reported that furosemide was even detrimental in the protection of renal dysfunction after CS 16 . The incidence of AKI after CABG was related to the use of preoperative furosemide, which increased exponentially with the increase of cumulative dose of furosemide 17 . The meta‐analysis by Winther et al 18 found that furosemide treated had no statistically significant difference on the incidence of AKI, need for renal replacement therapy (RRT) rate, and all‐cause mortality in adult surgical patients.…”
Section: Introductionmentioning
confidence: 99%